First person - Phillipe O'Brien, Kai Guo, Stephanie Eid, Amy Rumora and Lucy Hinder (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Phillipe O'Brien, Kai Guo, Stephanie Eid, Amy Rumora and Lucy Hinder are first authors on 'Integrated lipidomic and transcriptomic analyses identify altered nerve triglycerides in mouse models of prediabetes and type 2 diabetes', published in DMM. Phillipe, Stephanie, Amy and Lucy are all postdoctoral researchers in the lab of Eva L. Feldman at the University of Michigan, MI, USA, investigating the pathogenesis of peripheral neuropathy using mouse models of obesity and diabetes. Kai is a postdoctoral researcher in the lab of Junguk Hur at the University of North Dakota, Grand Forks, ND, USA, and uses high-throughput genomic data analysis to understand the development of neurological disorders.